Decolonization of Arctic Library and Archives Metadata (DALAM) Thematic Network Update: September 2023 - Campbell, Sandra M. (2023)
This is the Septermber 2023 Activities Update of the University of the Arctic DALAM (Decolonization of Arctic Library and Archives Metadata ) thematic network.